2008
DOI: 10.2106/jbjs.g.01353
|View full text |Cite
|
Sign up to set email alerts
|

Results of Internal Fixation of Pauwels Type-3 Vertical Femoral Neck Fractures

Abstract: Despite timely, excellent reduction and accurate implant placement in the vast majority of cases, the nonunion rate was 19% for fractures treated with cannulated screws alone and 8% for those treated with a fixed-angle device. Although these failure rates are not significantly different, we believe that this study documents the challenging nature of this fracture pattern and the ideal fixation device remains undefined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
242
3
12

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(260 citation statements)
references
References 15 publications
3
242
3
12
Order By: Relevance
“…These cases benefit most from open reduction and valgus osteotomy with or without fibular grafting. Higher Pauwelstype fractures have a greater chance of failure and varus collapse [12,17]. It has been suggested that such fracture nonunions are best treated by valgus osteotomy to improve biomechanics at the fracture site [12].…”
Section: Discussionmentioning
confidence: 99%
“…These cases benefit most from open reduction and valgus osteotomy with or without fibular grafting. Higher Pauwelstype fractures have a greater chance of failure and varus collapse [12,17]. It has been suggested that such fracture nonunions are best treated by valgus osteotomy to improve biomechanics at the fracture site [12].…”
Section: Discussionmentioning
confidence: 99%
“…Aminian et al [21], in a cadaveric study, found that the proximal femoral locking plate is the strongest construct for stabilizing a vertical shear femoral neck fracture, whereas three cannulated screws comprise the weakest construct; however, the nature of these fracture patterns makes them more susceptible to varus, shortening, and nonunion [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, in a retrospective review, 23% of patients treated with parallel screws developed nonunion or avascular necrosis compared to 59% of those treated with crossed/Pauwel screws [15]. In a subgroup analysis of the study by Liporace et al, mechanical failure occurred in 60% of fractures fixed with crossed/Pauwel screws compared to 13% of those fixed with parallel screws [16]. Another departure from the traditional inverted triangle configuration is the use of triangular parallel screws, which feature 2 inferior screws and 1 superior screw.…”
Section: Biomechanical Studiesmentioning
confidence: 98%
“…Liporace et al performed a retrospective review of 62 young (age range 19-64) patients with mostly displaced vertical femoral neck fractures [16]. These authors compared a heterogeneous group of fixed angle devices to a heterogeneous group of screw configurations.…”
Section: Clinical Studies: Comparativementioning
confidence: 99%